(untitled) (Tanzania Medical Journal, 2025)
Introduction: Understanding the factors that influence antimicrobial prescription decisions among healthcare providers is essential for designing more effective antimicrobial stewardship programs to combat antimicrobial resistance (AMR). Methodology: We conducted a cross-sectional study utiliZing a questionnaire among healthcare providers (doctors, pharmacists, nurses, and laboratory personnel) in Tanzania to explore their knowledge and attitudes towards AMR and antimicrobial use (AMU), as well as the factors influencing their prescribing and dispensing practices. The survey collected information on their educational and professional backgrounds, fields of clinical practice, sources of information on AMR and AMU, and factors influencing their decision-making. Descriptive statistics were used to report healthcare practitioners' levels of practice, knowledge, and attitudes toward AMR and AMU. Binary logistic regression was used to associate sociodemographic attributes with AMR and AMU knowledge. Results: Among 138 participants, 37.7% (n=52) were female, with a mean age of 37 ± 10.5 years. AMR/AMU training in the past year was reported by 45.7% (n=63). The main sources of information were the World Health Organization (WHO) guidelines 21.4% (n=71) and national guidelines 20.2% (n=67). Key factors influencing antimicrobial prescriptions were the ready availability at the local level 68.8% (n=95), the potential rise of resistant bacteria 57.2% (n=79), and the economic status of the client 55.1% (n=76). Respondents reported high levels of knowledge in selecting routes of administration 63.8% (n=88) and interpreting microbiological results 63.0% (n=87). In contrast, lower awareness was reported for the National Action Plan for AMR 29.3% (n=40) and the reserve category of antimicrobials 37.7% (n=52). The knowledge scale demonstrated high reliability (Cronbach's alpha = 0.92). Binary logistic regression analysis showed that being a nurse (AOR = 0.10, p = 0.043) and being a laboratory scientist (AOR = 0.27, p = 0.026) were significantly associated with lower knowledge of AMR/AMU. Conclusion: This study reveals gaps in knowledge and awareness of AMR and AMU among healthcare providers in Tanzania, particularly regarding the National Action Plan and the WHO reserve group of antimicrobials. These findings underscore the need for targeted education and professional development, especially for nurses and laboratory scientists, to strengthen antimicrobial stewardship and reduce AMR risk.